Nico Olivo: capstone - Olivo, Nico, artist (Colorado State University. Libraries, 2023)
The artist's statement: During my time here I have taken my time exploring the topic of love and intimacy in my practice through the lens of a queer man. I find it important to explore the topic of romance and relationships from a queer perspective due to the representation of queer love having been mostly from a cis, straight lens. This causes both the demonization and fetishization of the queer community and queer relationships. I have taken to exploring romantic love and all of the complex feelings that might arrive in different relationships. Love is so complex and unique that I find that capturing these ever evolving feelings to be an intuitive and introspective process is really just reaching out to be understood.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing